The Influence of Organizational Culture, Leadership, and Performance Management on Employee Work Ethic: Evidence from the Indonesia Eximbank (LPEI) Jakarta - Subroto Subroto (Priviet Social Sciences Journal, 2022)
This study aims to determine how much influence of cultural organization, leadership and performance management have on work ethic of employee. In this study using survey and observation of the object being investigated and used the questionnaire as the principal data collection tool. Data were collected by distributing questionnaires consisting 46 statement among other things 16 questionnaires cultural organizations, 9 questionnaires leaderships, 9 questionnaires performance management and 12 questionnaires work ethic of employee, questionnaire given to 130 respondents, which can be processed a total of 117 respondents. In this research, analytical testing to determine the significance of regression coefficients and for the cultural organization of 1.229 was obtained t> ttable 1.671, 1.400 t for the leadership gained> ttable 1.671, for the performance management obtained t 1.208> 1.671 ttable and jointly acquired t 2.216> 1.671 ttable also used a simple correlation coefficient analysis to determine whether there is influence of cultural organization, leadership and performance management have on work ethic of employee within Export Financing Indonesia Agency (LPEI) Jakarta. From the results of regression analysis (r) for the cultural organization of 0.114 indicates low influence, meanwhile 0.129 and 0.112 of leadership and performance management showed a strong influence. Value of determination (r2) shows the contribution provided by the cultural organization of 01.3%, 01.7% leadership and performance management 01.3%, affecting work ethic of employee. The coefficient of determination of 0.013 or 01.3% obtained from the cultural organization affects work ethic of employee, 0.017 or 01.7% obtained from the leadership affects work ethic of employee, 0.013 or 01.3% obtained from the performance management affects work ethic of employee and 0.029 or 02.9% jointly the cultural organization, leadership and performance management affect the work ethic of employees, while other factors influenced the rest.